Prototype-Guided Trust Calibration in Distributed Advertising Intelligence Systems: A Defense Framework Against Malicious Participant Manipulation (International Journal of Artificial Intelligence Engineering and Systems, 2026)
Distributed advertising intelligence systems rely on heterogeneous participants to contribute data, model updates, and behavioral signals that collectively drive ad targeting and performance optimization. However, the open and decentralized nature of these systems exposes them to adversarial manipulation, where malicious actors inject poisoned data or model perturbations to bias outcomes in their favor or degrade system integrity. Existing defenses, including anomaly detection and robust aggregation, often assume static threat models and fail to adapt to evolving attack strategies. This paper proposes a defense framework termed prototype-guided trust calibration, which leverages learned prototype representations of honest participant behavior to dynamically adjust trust scores and filter malicious contributions. The framework integrates principles from prototype-based learning, split learning defenses, and compliance-oriented governance architectures to create a layered protection mechanism. We examine structural trade-offs among detection accuracy, computational overhead, and system scalability, and discuss deployment considerations across multi-tenant advertising infrastructures. The framework further incorporates incentive alignment and content governance using standardized policy languages, enabling continuous calibration without centralizing trust. Cross-domain comparisons with federated learning secure aggregation and path-level model intervention demonstrate the distinct advantages of prototype-driven approaches in dynamic adversarial settings. Policy implications for platform accountability, auditability, and fairness are analyzed, along with future directions for trust calibration in large-scale socio-technical systems.
Keywords: distributed advertising intelligence; trust calibration; prototype-based defense; adversarial manipulation; content governance; multi-tenant infrastructure; incentive systems